USING COMMUNICATION CUE PARAMETER TO MEASURE POTENTIAL INTERACTION RISKS ON TINDER DATING APP - Maharani, Putri (Ma Chung Press, 2025)
This study examines communication styles and their moral implications on Tinder within the disruptive online dating landscape, focusing on Indonesian cultural dynamics. The paper aims to identify user communication patterns, motivations, and moral concerns on Tinder, especially risks faced by female users in Indonesia. Using a qualitative approach, the data were gathered through participant observation. Users were classified into three main groups, including generic and casual responders, direct and explicit communicators, and deceptive scammers, in addition to another category of non-responders. Communication often lacked authenticity, focusing on short-term goals. The study found significant moral degradation that leads to potential risks toward safety, particularly for women. It produces an identification graph of language cues that signal user intent, which can be used to enhance digital safety and protect against scams, harassment, and exploitation. Based on the findings, this study recommends the need for heightened awareness, education, and policy improvements for safer online dating. It advocates for increased user vigilance, especially for women, and suggests that identifying linguistic cues could enhance digital safety against scams and harassment.